Participerende Kolonialisme? 1800-tallets Aabenraasøfart i globalt perspektiv - Jespersen, Mikkel Leth (Temp - tidsskrift for historie, 2014)
Participating Colonialism? 19th Century Aabenraa Shipping in a Global Perspective The article analyses the shipping tradition of 19th century Aabenraa and discusses, whether it can be characterized as participating colonialism. Based on experience from European long distance shipping in the 18th century and a local shipbuilding tradition of high quality, the ships from Aabenraa began sailing to Brazil around 1820. The British had opened the former Portuguese colony for other nation’s trade and shipping. In the 1830’s and 40’s a greater number of Aabenraa ships sailed to Rio de la Plata and round Cape Horn, and when gold was found in California in 1848 they sailed all the way up to San Francisco. In China The First Opium War (1839-42) had opened new possibilities, and around 1850 the ships from Aabenraa seems to have preferred the Fareast over America. In the East other possibilities also opened up in a number of British colonies; Calcutta, Hong Kong and Australia. In the 1860’s and 70’s the ships from Aabenraa specialized in coastal shipping in China, and at the same time a small number of Aabenraa schooners were sailing on the Cape Coast. When the British formal and informal colonialism opened new possibilities the ships from Aabenraa followed. Therefore it can be said that the ships from Aabenraa participated in the British colonialism.